HUBUNGAN ANTARA KETERATURAN MINUM TABLET TAMBAH DARAH DAN POLA MAKAN IBU HAMIL DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS PEMBANTU DESA KUTALIMAN KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS 2009 - Supadi, Supadi (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2010)
ABSTRACT About 70 % of pregnant mother in Indonesia suffering anemia. Anemia is acommon problem in the world and affecting more that 600 millions peeople, which is still in high frequency, about 10 to 20 %. At Kutaliman village, pregnant mothers who suffered anemia were 54 (40%) of 130 pregnant mothers from January to December 2008. This research has objective to explore the correlation between regularity of oral iron supplement intake and eating pattern and anemia incidence in pregnant mother. This was analitycal study with cross sectional design. The result with chisquare test showed that there was a correlation between regularity of oral iron supplement intake and eating pattern and anemia incidence, p value was 0.001. Pregnant mother who had regular iron supplement intake were 27 (65.9%), and 14 had irregular iron supplement intake (34.1%), pregnant mothers with inadequate eating pattern were 28 (68.3%) and adequate eating pattern were 13 (31.7%). Haemoglobin level (39%) were less than 11 gr%. There was a correlation between regularity in iron supplement intake and mother eating pattern and anemia incidence. Keyword : eating pattern, iron supplement, anemia.  Kesmasindo Volume 3, Nomor 1, Januari 2010, hlm. 19-33